Vicia faba determinate and indeterminate inflorescence genotypes : comparison of genetic variation at TFL1 locus - Östberg, Jenny (SLU/Dept. of Plant Breeding (from 130101), 2021)
Faba bean (Vicia faba L.) plants usually express an indeterminate inflorescence growth habit regulated by the gene TERMINAL FLOWER1 (TFL1) which allows the apical meristem to continuously produce new vegetative and reproductive plant parts. In turn, this prolongs the growth and flowering period and causes an uneven ripening of the pods. The opposite growth habit is determinate inflorescence where the apical meristem evolves into a terminal inflorescence which can give a more homogenous ripening of pods, a trait desired for its agronomical benefits especially in a northern country like Sweden where the growing season is relatively short. In this study, the TFL1 gene and part of its upstream region was amplified, sequenced and analysed from genomic DNA of eleven different faba bean varieties with previously described growth habit, indeterminate or determinate, to explore the genetic variation between the varieties. The aim was to find a genetic molecular marker which could be used in plant breeding of new cultivars better adapted for short growing seasons. Several SNPs were identified in the upstream region of TFL1 and were shown to be shared by varieties of the same inflorescence growth habit, but no observed sequence difference was clearly separating all the determinate varieties from the indeterminate. One of the mutant varieties showed an SSR which distinguished it from all other varieties in this study. These findings propose that there might be more than one genetic variation in the TFL1 locus which could cause the determinate inflorescence growth habit in determinate faba bean varieties.